Ultrafine Copper Nanopalm Tree‐Like Framework Decorated with Iron Oxide for Li‐Ion Battery Anodes with Exceptional Rate Capability and Cycling Stability. Issue 13 (14th February 2019) - Seok, Jae Young; Lee, Jaehak; Park, Jung Hwan; Yang, Minyang
Abstract: Ultrafine copper nanopalm tree‐like frameworks conformally decorated with iron oxide (Cu NPF@Fe2 O3 ) are prepared by a facile electrodeposition method utilizing bromine ions as unique anisotropic growth catalysts. The formation mechanism and control over Cu growth are comprehensively investigated under various conditions to provide a guideline for fabricating a Cu nanoarchitecture via electrochemical methods. The optimized Cu NPFs exhibit ultrathin (<90 nm) and elongated (2–50 µm) branches with well‐interconnected and entangled features, which result in highly desirable attributes such as a large specific surface area (≈6.97 m 2 g −1 ), free transfer pathway for Li +, and high electrical conductivity. The structural advantages of Cu NPF@Fe2 O3 enhance the electrochemical kinetics, providing large reactivity, fast Li + /electron transfer, and structural stability during cycling, that lead to superior electrochemical Li storage performance. The resulting Cu NPF@Fe2 O3 demonstrates a high specific capacity (919.5 mAh g –1 at 0.1 C), long‐term stability (801.1 mAh g –1 at 2 C, ≈120% retention after 500 cycles), and outstanding rate capability (630 mAh g –1 at 10 C). Abstract : An ultrafine copper nanopalm tree‐like framework (Cu NPF) having a thin diameter (≈85 nm) and elongated (2–50 µm) branches is prepared by facile one‐step electrodeposition utilizing bromine as an anisotropic growth catalyst. The palm tree‐like Cu architecture significantly enhances the electrochemical kinetics; the resulting structured electrode demonstrated high specific capacity, and outstanding rate capability and cycling stability.